2020
DOI: 10.1002/edm2.167
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the prevalence of thyroid dysfunction in Catalonia through two different registries: Pharmaceutical dispensing and diagnostic registration

Abstract: Summary Background Population studies on the prevalence of thyroid dysfunctions are costly. The pharmacy dispensing (PDR) and diagnosis (DR) registers allow us to study the epidemiology of these pathologies in a simpler way. Our aims: 1/Estimate the prevalence of thyroid dysfunction in Catalonia based on data from the PDR and the DR, 2/to evaluate the concordance of the results obtained by both strategies. Methods The population studied was the one registered with the public health system in Catalonia(Catsalut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…did, the percentage of hypothyroidism is 4.8%, which is higher. In the case of hyperthyroidism, the results obtained in this study are similar to the range identified by Torrejón for women aged between 30 and 50 years old (0.54%) ( 13 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…did, the percentage of hypothyroidism is 4.8%, which is higher. In the case of hyperthyroidism, the results obtained in this study are similar to the range identified by Torrejón for women aged between 30 and 50 years old (0.54%) ( 13 ).…”
Section: Discussionsupporting
confidence: 90%
“…The epidemiology of thyroid disorders depends on multiple factors such as nutritional iodine intake and thyroid autoimmunity. However, the Catalan population fulfils the iodine intake of WHO recommended standards ( 1 , 5 , 13 15 ). Although the TPOAb prevalence detected was relatively high in the UTD group (16.92%), it could be associated with an adequate level of iodine status in the population ( 16 ), which is very similar to that obtained in Catalan women by Vila et al.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Unfortunately, we have a lack of knowledge on the incidence of GD in Spain and only have data about the estimated prevalence of 0.8% 19 of the population being diagnosed with hyperthyroidism and 0.14% receiving antithyroid treatment. 20 …”
Section: Discussionmentioning
confidence: 99%
“…This variability responds to the strong genetic component in the likelihood of developing GD, which is estimated at 79%, 16 but many other risk factors have been associated with autoimmune thyroid disorders involving T‐cell dysfunction, among which smoking stands out with an odds ratio of 1.9, 17 or iodine intake 18 . Unfortunately, we have a lack of knowledge on the incidence of GD in Spain and only have data about the estimated prevalence of 0.8% 19 of the population being diagnosed with hyperthyroidism and 0.14% receiving antithyroid treatment 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation